The Impacts of Online Games on Students’ English Achievement - Muthmainnah Mursidin; Ida Ilmiah Mursidin; Asrang (CV. ADIBA AISHA AMIRA, 2021)
Focus of the research is to know the analysis of online games on Students English Achievement. Therefore the researcher formulated a research question what are the impact of online game on students English achievement? This research used qualitative method and analysis of Online Games. The researcher used interview and documentation in collecting the data. The objective of the research showed that To investigate the impact of online games on students achievement The research result is the impact of online games on learning English, based on findings in the field, it can be concluded that students have difficulty finding good learning conditions especially during this pandemic because it requires students to learn Via Online, students experience problems in managing independent learning time, doing assignments so you play more often. In terms of learning English, play online games has a huge influence on students' learning patterns and think patterns, how students write, especially in the sentence write section because English has a difference between pronunciation and write, but along with technological developments that make it easier for students to write